Development of the Iron Electrode for Utility Scale Energy Storage - , (2019)
Iron electrodes, used in Nickel Iron (NiFe) batteries, are known for their electrode stability, 25-year cycle life and suitability for utility scale energy storage. Key challenges addressed here include rapid electrode manufacture, analytical techniques and, cathodic hydrogen evolution. Electrode manufacture was investigated in order to produce a low-cost iron electrode suitable for scale up. Ultrafast heating techniques, including near infrared, were used to produce electrodes on substrates with various surface modifications. Low temperature PTFE bound electrodes and sintered electrodes were produced via rapid heating. Electrochemical testing showed mixed results with sintered electrodes cycling successfully and no discernible effect from substrate surface modification. The in-situ Scanning Vibrating Electrode Technique (SVET) has been used here for the first time in energy storage to study the parasitic hydrogen evolution reaction (HER) which occurs during charging and compromises round trip efficiency. SVET was used to map HER current density distribution across an iron electrode with respect to time and accuracy was verified against a traditional gas collection technique. Thiourea was shown to offer a 92% reduction in hydrogen evolution and the SVET was also shown to operate on sintered iron electrodes manufactured in earlier work. The Scanning Kelvin Probe was used on iron electrodes to spatially resolve the Volta potential depression effect which occurs due to presence of atomic hydrogen. The mechanisms of HER inhibitors, benzotriazole and thiourea were compared against those described in literature. Differing mechanisms were confirmed, further demonstrating the potential of scanning electrochemistry in energy storage research.